2017
DOI: 10.1038/s41598-017-09518-1
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of Pharmacokinetic Profile of TRAIL via Trimer-Tag Enhances its Antitumor Activity in vivo

Abstract: TNF-related apoptosis-inducing ligand (TRAIL/Apo2L) has long been considered a tantalizing target for cancer therapy because it mediates activation of the extrinsic apoptosis pathway in a tumor-specific manner by binding to and trimerizing its functional receptors DR4 or DR5. Despite initial promise, both recombinant human TRAIL (native TRAIL) and dimeric DR4/DR5 agonist monoclonal antibodies (mAbs) failed in multiple human clinical trials. Here we show that in-frame fusion of human C-propeptide of α1(I) colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 55 publications
2
71
0
Order By: Relevance
“…Some death ligands include Fas ligand (Fas-L), TNF-related apoptosis-inducing ligand (TRAIL) and tumor necrosis factor (TNF) [ 13 ]. An adaptor protein is recruited to the death receptor [ 4 , 14 ]; adaptor proteins include Fas-associated death domain (FADD) and TNF receptor-associated death domain (TRADD) [ 13 ]. Initiator procaspases-8 and -10 bind to the adaptor protein, forming the death-inducing signaling complex (DISC) [ 4 , 14 ].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…Some death ligands include Fas ligand (Fas-L), TNF-related apoptosis-inducing ligand (TRAIL) and tumor necrosis factor (TNF) [ 13 ]. An adaptor protein is recruited to the death receptor [ 4 , 14 ]; adaptor proteins include Fas-associated death domain (FADD) and TNF receptor-associated death domain (TRADD) [ 13 ]. Initiator procaspases-8 and -10 bind to the adaptor protein, forming the death-inducing signaling complex (DISC) [ 4 , 14 ].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…For example, the University of Queensland is developing a subunit vaccine based on the "molecular clamp" technology [44]. Clover Biopharmaceuticals Inc. revealed that they are developing a vaccine candidate against SARS-CoV-2 using the "Trimer-Tag" technology [45], and the trimeric S protein subunit vaccine candidate was produced via a mammalian cell expression system. Novavax, Inc. announced that they had produced multiple nanoparticle vaccine candidates based on S protein, and now is assessing efficacy in animal models to identify an optimal vaccine candidate for human testing.…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…Their docking was then carried out in order to obtain the best match based on the total free enthalpy (or score) value. The soluble TRAIL was chosen in its cristallographic trimerized structure, because it is its most stable natural state and was used as such during docking calculations . Then, docking simulations were performed progressively by adding the receptor to the optimized TRAIL trimer, one by one.…”
Section: Resultsmentioning
confidence: 99%
“…The soluble TRAIL was chosen in its cristallographic trimerized structure, because it is its most stable natural state and was used as such during docking calculations. 35 Then, docking simulations were performed progressively by adding the receptor to the optimized TRAIL trimer, one by one. The scoring energies were then classified and the crystallographic structure was compared with the best scoring structure.…”
Section: Interaction Of Trail With Drsmentioning
confidence: 99%